Selection of a minimum fracturation area by means of geotastics for emplacement of subsurface civil Works of a nuclear repository in crystalline rock - Girardi, J. P.; Matar de Serquis, M. (Comisión Nacional de Energía Atómica; Argentina, 1987)
Fil: Girardi, J. P. Instituto de Investigaciones Mineras. Universidad Nacional de San Juan; Argentina